STUDY OF CORRELATION OF INTENSITY OF SYMPTOMS WITH STRESSFUL LIFE EVENTS IN DEPRESSED PATIENTS - Mahatme, S.S. (Medknow Publications, 1989)
60 patients suffering from “Depression” attending the Psychiatry outpatient clinic in a general hospital were studied. The intensity of symptoms, and life stress events for 12 months prior to episode were obtained and compared on the basis of sex of patient. The findings of the study indicate that, the depressed patients had the severity of symptomatology positively correlated with the severity of stress. Thus with the increase in stress, the severity of symptoms would be on increase. The findings also indicated the distribution of more physical and affective symptoms in depressed females and more of behavioural symptoms in depressed males. It was seen that occurrence of undesirable life events which could be specific for Indian culture were perceived more than desirable events by the sample.